A qualitative study of evidence-based therapeutic process in mental health services in Ghana- context-mechanisms-outcomes - Eric Badu; Anthony Paul O'Brien; Rebecca Mitchell; Akwasi Osei (BMC, 2021)
Abstract Background Evidence-based clinical practice is an inherent component of mental health professional practice in developed countries. However, little is known about professional perspectives of evidence-based practice in mental in developing countries such as Ghana. This paper describes the processes involved in the delivery of best practice in Ghana. The paper reports on a realistic evaluation of mental health nurses and allied health professionals' views on the evidence-based therapeutic process in Ghana. Methods A purposive sample of 30 mental health professionals (MHPs) was recruited to participate in semi-structured, in-depth interviews. Thematic analysis was used to analyse the data. A program theory of Context + Mechanism = Outcome (CMO) configuration was developed from the analysis. Results The thematic analysis identified two contexts, mechanism and outcome configurations (themes): 1) technical competency stimulates evidence-based mental health services, and 2) therapeutic relationship building ensures effective interaction. The study demonstrates that contextual factors (technical competencies and therapeutic relationship building) together with mechanisms (intentional and unintentional) help to promote quality in mental health service provision. However, contextual factors such as a lack of sign language interpreters yielded unintended outcomes including barriers to communication with providers for consumers with hearing impairment and those from linguistic minority backgrounds. Conclusion Government stakeholders and policymakers should prioritise policies, periodic monitoring and adequate financial incentives to support the mechanisms that promote technical competence in MHPs and the building of therapeutic relationship.